Phenotypic characterization of PIGN–associated paroxysmal dyskinesia in Soft-coated wheaten terriers and preliminary response to acetazolamide therapy. (March 2021) - Packer, R.A.; Wachowiak, I.; Thomovsky, S.A.; Berg, J.; Vasquez, L.; O'Brien, D.P.
Highlights: A paroxysmal dyskinesia has been identified in soft-coated wheaten terriers. A homozygous mutation in the PIGN gene is associated with this phenotype. Acetazolamide (carbonic anhydrase inhibitor) treatment is effective in many dogs. Abstract: A hereditary movement disorder in Soft coated wheaten terriers (SCWT) has been associated with a mutation in PIGN which encodes an enzyme involved in synthesis of glycosylphosphatidylinositol (GPI). The objective of this study was to describe and classify the clinical phenotype and assess therapeutic response. Twenty-five SCWT and related dogs homozygous for PIGN:c.398C>T with paroxysmal dyskinesia were available for inclusion. Medical records and video recordings of 17 dogs were evaluated in a retrospective case series. Affected dogs had episodes of involuntary, hyperkinetic movements and dystonia. Median age of onset was 2.5 years. A typical episode consisted of rapid, irregular hyperflexion and extension of the pelvic limbs with some degree of truncal dystonia. A mild episode consisted of spontaneous flexion of one pelvic limb while walking which could resemble a lameness. Episodes lasted several minutes to several hours and occurred up to 10 times/day or more. They were not associated with exercise or fasting but were sometimes triggered by excitement or stress. Acetazolamide therapy improved nine of 11 dogs, in seven cases abolishing episodes. Five of 17 dogs treated with other agents had mild improvement with clonazepam ( n = 2), levetiracetam ( n = 1), or phenobarbital ( n = 2). Paroxysmal dyskinesias must be differentiated from seizure disorders since they often respond to different therapies. The SCWT phenotype consisted predominantly of hyperkinesia, and can respond dramatically to acetazolamide. GPI anchors proteins to the cell surface including carbonic anhydrase IV which modulates synaptic pH in the brain. Altered activity of this enzyme may be the target of acetazolamide therapy.